Supporting Newcomer Youth Through the Process of School Integration in Canada: A Brief Report Highlighting Student Voices - Smith, Danielle J.; Kassan, Anusha; Mudry, Tanya E.; Mukred, Rabab; Goopy, Suzanne (Canadian Journal of Counselling and Psychotherapy, 2022)
Given that an increasing number of newcomer youth enter high schools in Canada each year, educational settings are faced with the challenge of creating programming and policies that promote a positive integration process. As part of a larger study that examined the integration experiences of newcomer youth, four participants were asked to offer advice for other newcomer students and for professionals working with this group and suggestions of ways to improve the current educational system. Analysis of these suggestions revealed four themes: (a) forming connections, (b) support from professionals, (c) appropriate placement, and (d) provision of additional resources and information. These themes highlight areas in which newcomer youth are lacking support and provide practical solutions to ensure that newcomer youth feel more connected to their schools and communities and supported through the process of school integration.